Investigation of efficacy of low length-to-diameter ratio and nozzle pressure ratio on base pressure in an abruptly expanded flow - Ahmed, Fharrukh; Khan, Sher Afghan (EDP Sciences, 2018)
This study has been carried out to assess the efficacy of the flow regulations in the form of tiny jets to regulate the pressure in the base region of an abruptly expanded duct. Four tiny jets of 1mm diameter placed at 90 intervals at 6.5 mm distance from the main jet in the wake region of the base were employed as flow management mechanism. The experiments were conducted at the inertia level of M = 2.5 & 3.0. The jets from the nozzles were expanded abruptly into a circular duct with four cross-sectional areas of 2.56, 3.24, 4.84 and 6.25. The L/D ratio of the enlarged duct considered was from 10 to 1 and experiments were conducted for Nozzle Pressure Ratio (NPR) from 3 to 11. Since the jets Mach numbers are high and the highest NPR tested was 11 which imply that the flow remains over expanded, even though, with increase in the NPR, the level of over expansion will decrease. It is well known that for over expanded nozzles an oblique shock will be formed at the nozzle lip, which in turn will result in the increase of the base pressure once it passes through the shock wave. From the results it is observed that for the NPRs 3 and 5 there is no appreciable gain in the base pressure, and hence, control employed as tiny jets are not effective, however, at NPR 7, 9, and 11 there is remarkable change in the base pressure values. This clearly indicates that NPR plays a significant role to decide on the magnitude of the base pressure and the control efficacy of the flow regulation mechanism as the tiny jets. It is found that the present method of flow regulation mechanism can be used as effective regulator of the base flows in an abruptly expanded duct. The control does not alter the nature of the flow in the enlarge duct.